Routing subject to quality of service constraints in integrated communication networks. - Lee, W.C (IEEE Network : the magazine of global information exchange)
With increasingly diverse QOS requirements, it is impractical to continue to rely on conventional routing paradigms that emphasize the search for an optimal path based on a predetermined metric, or a particular function of multiple metrics. Modern routing strategies must not only be adaptive to network changes but also offer considerable economy of scope. We consider the problem of routing in networks subject to QOS constraints. After providing an overview of prior routing work, we define various QOS constraints. We present a call architecture that may be used for QOS matching and a connection management mechanism for network resource allocation. We discuss fallback routing, and review some existing routing frameworks. We also present a new rule-based, call-by-call source routing strategy for integrated communication networks